2005
DOI: 10.1097/01.mao.0000169042.25734.97
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Test for Ménière's Disease and Cochlear Hydrops: Impaired High-Pass Noise Masking of Auditory Brainstem Responses

Abstract: This test is able to distinguish objectively active Ménière's disease in individuals and may show promise for tracking changes in the severity of the disease caused by progression or treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(102 citation statements)
references
References 34 publications
6
93
2
1
Order By: Relevance
“…Another parameter of this test, in addition to wave V latency, is the complex amplitude ratio (CAR). An abnormal CAR value (CAR value below 0.95) has been suggested to have 95% specificity and 90% sensitivity (24,25). It is claimed that the CHAMP test can demonstrate not only the presence of active MD but also the progress of the disease in treatment and follow-up periods.…”
Section: Brainstem Auditory-evoked Potentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another parameter of this test, in addition to wave V latency, is the complex amplitude ratio (CAR). An abnormal CAR value (CAR value below 0.95) has been suggested to have 95% specificity and 90% sensitivity (24,25). It is claimed that the CHAMP test can demonstrate not only the presence of active MD but also the progress of the disease in treatment and follow-up periods.…”
Section: Brainstem Auditory-evoked Potentialsmentioning
confidence: 99%
“…Prolonged latency, decreased amplitude or complete disappearance of the wave I, prolonged latencies between waves, or impaired wave morphology are the typical findings observed in cochlear pathologies, but they are valuable for MD only in the differential diagnosis of retrocochlear pathologies (23). For the diagnoses of EH and MD, an ABR technique called "cochlear hydrops analysis masking procedure" (CHAMP) has been introduced (24). The CHAMP test is the measurement of the difference between the wave V latency obtained with a single-click stimulus and the wave V latency obtained in the presence of a masking noise at 0.5 kHz frequency in addition to a click stimulus.…”
Section: Brainstem Auditory-evoked Potentialsmentioning
confidence: 99%
“…This is an auditory brainstem response (ABR) test that is masked with high-pass noise. MD patients display a shortened latency in Wave V. A Californian group has been able to show with 100% sensitivity and 100% specificity a difference between controls and active MD patients displaying at least three of the four core symptoms [12]. However, later studies have failed to repeat such impressive results.…”
Section: Electronystagmographymentioning
confidence: 86%
“…Don et al conducted the test in 23 definite MD patients and compared the results with 38 non-MD normal-hearing subjects. Their measures did not demonstrate an overlap between the Ménière's and nonMénière's groups, and therefore, the authors concluded that the test had an extremely high, even 100%, sensitivity and 100% specificity for diagnostic use in individual patients [34].…”
Section: Electrophysiology Inmentioning
confidence: 99%
“…The latency delay in normal-hearing ears, between wave V for the click alone response and the 0.5 kHz high-pass masking noise condition, is significantly longer than that in MD ears. This difference is known as the latency delay [34].…”
Section: Cochlear Hydrops Analysis Masking Procedures (Champ)mentioning
confidence: 99%